2019
DOI: 10.1016/j.celrep.2019.09.069
|View full text |Cite
|
Sign up to set email alerts
|

STING-Mediated IFI16 Degradation Negatively Controls Type I Interferon Production

Abstract: Highlights d Overexpression of STING facilitates IFI16 degradation d E3 ligase TRIM21 plays a role in STING-mediated IFI16 degradation d IFI16-K3/4/6R mutation stabilizes IFI16 protein d IFI16-K3/4/6R facilitates type I IFN production

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 59 publications
1
53
0
Order By: Relevance
“…Therefore, it is inferred that during viral infection, IFI16 can facilitate recognition of decapsidated viral DNA in the nucleus, while cGAS in the cytoplasm engages with viral gene transcription products (104,108). However, STING signaling can trigger IFI16 degradation by tripartite motif-containing 21 (TRIM21) ubiquitination (109).…”
Section: Cross-regulation Of the Cgas-sting Pathway With Other Dna-sementioning
confidence: 99%
“…Therefore, it is inferred that during viral infection, IFI16 can facilitate recognition of decapsidated viral DNA in the nucleus, while cGAS in the cytoplasm engages with viral gene transcription products (104,108). However, STING signaling can trigger IFI16 degradation by tripartite motif-containing 21 (TRIM21) ubiquitination (109).…”
Section: Cross-regulation Of the Cgas-sting Pathway With Other Dna-sementioning
confidence: 99%
“…Recently, STING was shown to engage TRIM21, another E3 ubiquitin ligase, to degrade γ-interferon-inducible protein-16. 43 Our study revealed a novel B cell-intrinsic role of STING in regulating BCR signaling and plasma cell differentiation. Since continuous BCR signaling via repeated antigen binding is critical for driving plasma cell differentiation, insufficient BCR signaling in V154M B cells ( Fig.…”
Section: Discussionmentioning
confidence: 69%
“…TRIM21 mediates the polyubiquitination and degradation of the DNA sensor DDX41 and the IRF transcription factors IRF3, IRF5, and IRF7 to negatively regulate the production of interferon-β during viral infection [56]. Recent research reported that TRIM21 can also promote the STING-mediated IFI16 degradation and negatively regulate the production of type I interferon [57]. However, a growing number of studies have shown that TRIM21 positively upregulates type I IFN signaling through promoting cGAS and RIG-I sensing of viral genomes or interfering with the degradation of IRF3 and IRF8 [58,59].…”
Section: Discussionmentioning
confidence: 99%